Dehospitalization: pharmacoeconomic aspects and the impacts of days saved from hospitalization in renal transplant patients using carbapenems - Thaynara Carvalho DE FREITAS; João Antonio DE SOUSA; Alene Barros DE OLIVEIRA; Maria Gabrielle LINHARES; Cinthya Cavalcante DE ANDRADE; Evelyne Santana GIRÃO; Henry Pablo REIS (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Purpose: To carry out an analysis cost minimization and patient outcomes submitted to OPAT of carbapenems in a teaching hospital in the state of Ceará. Methodology: This is a descriptive and retrospective observational study with a quantitative, characterized as a pharmacoeconomic analysis of cost minimization of the treatment performed with meropenem in patients hospitalized in the renal transplant units of a teaching hospital in the state of Ceará and outpatients who migrated for OPAT with ertapenem in outpatient services. The clinical outcome was evaluated by measuring the readmission rate up to 30 days after the end of treatment. Results: Eight patients were selected for the study. The microbiological profile verified the predominance of infections caused by Enterobacteriaceae (Klebsiella pneumoniae and Escherichia coli), representing 75% of the microbiological isolates. The cost analysis found a daily cost of U$ 60.04 in the treatment conducted with meropenem in hospitalized patients, in contrast, the daily cost in OPAT performed with ertapenem was US$ 78.79. The treatments performed totaled a cost of U$ 7,515.89 for the institution, and in an unprecedented way we evidenced a cost reduced from US$ 1029.45 if the treatment were fully carried out during the hospitalization (US$ 6,484.44). Conclusion: There was an incremental cost during dehospitalization in relation to the treatment performed during hospitalization hospital, on the other hand, a higher bed turnover can be observed, which makes it possible to perform more transplants.